2013
DOI: 10.1186/1742-4933-10-18
|View full text |Cite
|
Sign up to set email alerts
|

Passive anti-amyloid immunotherapy in Alzheimer's disease: What are the most promising targets?

Abstract: Alzheimer’s disease (AD) is the most common dementia in the industrialized world, with prevalence rates well over 30% in the over 80-years-old population. The dementia causes enormous costs to the social healthcare systems, as well as personal tragedies for the patients, families and caregivers. AD is strongly associated with Amyloid-beta (Aβ) protein aggregation, which results in extracellular plaques in the brain, and according to the amyloid cascade hypothesis appeared to be a promising target for the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 71 publications
1
72
0
2
Order By: Relevance
“…In this sense, the use of antibodies directed against specific epitopes or conformations of Aβ has yielded promising results. Passive immunization approaches using monoclonal antibodies against Aβ1-40 [103], Aβ1-42 [104], pyroglutamate Aβ [105], oligomers [106], or protofibrils [107][108][109] have been developed. Currently, clinical trials with the antibodies BAN2401 (recognizing protofibrils) [75], crenezumab (aggregated species) [76], gantenerumab (fibrils) [78][79][80], and solanezumab (Aβ mid-domain) [81,82] are ongoing (Table 1).…”
Section: Immunotherapy Targeting Aβmentioning
confidence: 99%
“…In this sense, the use of antibodies directed against specific epitopes or conformations of Aβ has yielded promising results. Passive immunization approaches using monoclonal antibodies against Aβ1-40 [103], Aβ1-42 [104], pyroglutamate Aβ [105], oligomers [106], or protofibrils [107][108][109] have been developed. Currently, clinical trials with the antibodies BAN2401 (recognizing protofibrils) [75], crenezumab (aggregated species) [76], gantenerumab (fibrils) [78][79][80], and solanezumab (Aβ mid-domain) [81,82] are ongoing (Table 1).…”
Section: Immunotherapy Targeting Aβmentioning
confidence: 99%
“…Efficient treatment strategies are still limited and an aging society in demographic change presents an enormous challenge to the health systems of industrialized nations. Despite the extensive research and effort to uncover the mechanism of AD pathogenesis, more or less all drug candidates failed to demonstrate significant effects on cognition in clinical trials [3,4].…”
Section: Cns Delivery -An Unmet Medical Needmentioning
confidence: 99%
“…Currently, all biopharmaceuticals that are used or being evaluated in the clinics for CNS disease act predominantly via peripheral mechanism: e.g. anti-amyloid- (A) capturing monoclonal/polyclonal antibodies in AD [3,4] or immune cell regulating biopharmaceuticals in multiple sclerosis [11]. However, candidate biopharmaceuticals reveal promising results in cellular models or in animal models when delivered intracerebroventricular.…”
mentioning
confidence: 99%
“…However, recent clinical trials with these therapies showed no benefit, and, in some cases, caused harm 12 . An unexploited strategy to modulate Aβ production is to alter the sub-cellular localization of APP and γ-secretase interaction.…”
Section: Introductionmentioning
confidence: 99%